Legislaç\~oes e abordagens institucionais em violência contra as mulheres no sistema de justiça: Experiências na América Latina - Andrea Catalina León Amaya; Paola Stuker (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This current work deals with experiences in Latin America on the theme of violence against women, concerning legislation and institutional approaches in the justice system, focusing on six countries: Argentina, Brazil, Colombia, Costa Rica, Guatemala and Uruguay. The text is the product of a documental and bibliographic review for research design within the scope of the project The Judiciary in Confronting Domestic and Family Violence against Women, developed by Ipea in technical partnership with the National Council of Justice (CNJ). Based on the study of international documents, legislation and institutional and academic research on the subject, the normative and practical relations of the countries are presented to the international recommendations of the Committee of Experts (Cevi), of the Follow-Up Mechanism to the Belém do Pará Convention (MESECVI). Although there are adjustments to the international recommendations, the reflections guide to the strength of local elements in the application of the transnational, since structural and evaluative interpositions define normative and institutional distances.
Keywords: Z18; K38; 330; violence against women; justice system; Latin America